Integrasi Ilmu Sosial dan Humaniora dalam Studi Islam: Sebuah Kajian Multidisipliner - Amri Saputra; Lutfiah Holifa Balkis; M Nuzulul Ulum; Winda Islamitha Nurhamidah; Ahmad Arifi (Pusat Riset dan Inovasi Nasional, 2024)
This article discusses the integration of social sciences and humanities in Islamic studies as an epistemological reconstruction effort to restore the unity between revelation, reason, and social reality. The research approach used is qualitative with a library research design through critical analysis of academic literature from various sources, including journals indexed by Scopus and Google Scholar. The results of the study indicate that the integration of social sciences and humanities broadens the orientation of Islamic studies from a normative-theological perspective to a more contextual and transformative multidisciplinary analysis. The social sciences serve as analytical instruments for socio-religious phenomena, while the humanities provide a reflective, ethical, and philosophical foundation that enriches understanding of Islamic teachings. The implementation of this paradigm is evident in the concept of